Vivendo a utopia do presente: a cidade de Fortaleza na produção audiovisual do Coletivo Alumbramento (2006-2011) - Camurça, Rodrigo Capistrano (2018)
Regarding the cinematographic production developed in the state of Ceará, this research builds a reflection on the films made in and about the city of Fortaleza. The accelerated growth of the capital of Ceará in the last decades and the appearance of some training schools in the area of cinema production contributed for the more experienced filmmakers and the new directors to pay more attention to their urban practices and experiences, revealing, in the movies, a multiple city in places and characters, also desirous asserting itself as a metropolis. Updating this discussion for the first decade of the 21st century, we will dwell on the conditions and possibilities that guaranteed the creation of a collective group of audiovisual creation in Fortaleza, named Alumbramento. The research will focus on the operation of this group in its first phase of existence (2006-2011). We will bring up some films made by the collective that problematize the city, placing this one in the leading role of its operation movements. Arising from the concerns raised nowadays, an analysis will discuss what these directors sought to develop in their creative proposals and possible inventions. To do so, we will use as sources interviews with filmmakers, personal files, catalogs of presentations, magazines, newspapers and websites that have developed critical texts and reflections about this cinematographic universe. However, the films are the ones to play a central role in our analysis, as for they support us regarding the e materiality of some specific works and the extra physical environment.